Influence of the genesis of iron minerals in the development of metallurgical processes - Gonzáles, Jorge (2012)
Presently work is given to know the importance of the previous characterization of the diverse types of minerals of Fe. The importance of the metallurgical properties and its respective mineralogy characterization are important for the development of respective metallurgical processes appropriate. In this work, it is given to know mineralogy characterizations of diverse Minerals of Fe. These results can be useful, for example in the development of processes of direct reduction with Gas.